Carex brunnescens (Pers.) Poir. in Poland and in the neighbouring regions – in the past and at present - Kruk, Jerzy (Biodiversity: Research and Conservation, 2022)
In the article, new and historical locations of Carex brunnescens (Pers.) Poir. from Poland and the neighbouring regions are described. This species was found in 2019 at two stands in north-eastern Poland – on the peaty shores of two small lakes; one situated in the Suwałki Landscape Park and the other in the Augustów Forest. Three historical records, supported by the herbarium materials, from the turn of the 19th and the 20th centuries, were situated in the Lower Vistula region (north-central Poland), i.e. in the vicinity of Kielno, Nowe and Susz. The literature data indicates the existence of many stands in the historical Eastern Prussia, one of which was situated south of the Romnicka Forest in Poland and all the others in the Kaliningrad region. Moreover, numerous incorrect reports from the Sudetes and the Carpathians were discussed. As Carex brunnescens is probably extinct at all the historical locations in the present territory of Poland, the species deserves special attention and protection at the two recently indentified stands.